APPLICATION OF QUALITY BY DESIGN APPROACH FOR THE OPTIMIZATION OF ORODISPERSIBLE FILM FORMULATION - Gupta, Ashutosh; Kumar, Jatin; Verma, Surajpal; Singh, Harmanpreet (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study was done to understand the effect of formulation variables on the quality of orodispersible films using quality by design (QbD) approach as mentioned in ICH Q8 (R2) guideline. Methods: A definitive screening design of experiments (DoE) was used to identify and classify the critical formulation variables affecting critical quality attributes (CQA) using 2×2 factorial design. Based on prescreening study, the critical formulation variables, i.e. concentration of film-forming polymer and plasticizers (propylene glycol and polyethylene glycol 400 [PEG 400]) were kept in the range of 1.5–2.5% w/w and 0.5–1% v/v, respectively. A total of eight laboratory-scale formulations were prepared which were provided by DoE using solvent casting method. These batches were evaluated for CQA's, i.e. mechanical properties such as folding endurance (FD) and disintegration time (DT). Data were analyzed for elucidating interactions between two variables and for providing a predictive model for the process. Finally, the drug was incorporated into optimized batches, and these were evaluated for in vitro dissolution study in simulated saliva (pH 6.8) as well as their mechanical properties. Results: The results suggested that the concentration of film-forming polymer and plasticizer was critical to manufacture orodispersible film with desired CQA, i.e. mechanical property (FD [>150 folds]) and DT (<60 s). The percent drug release, FD, and DT of optimized Formulation I (hydroxypropyl methylcellulose [HPMC] E5 (2%) and propylene glycol [0.15 mL]) were found to be 82.13%±0.260 (in 15 min), 164±2, and 49±1.5 s, respectively, and for optimized Formulation II (HPMC E5 [2%] and PEG 400 [0.15 mL]) was found to be 64.26%±2.026 (in 15 min) and 218±6 and 55±4 s, respectively. Conclusion: From the results, it has been found that the percentage drug release of naratriptan hydrochloride containing propylene glycol as a plasticizer was greater than the formulation containing PEG 400 as plasticizer. From this, we concluded that QbD is very much useful approach to get an optimized formulation in an economic and faster way in comparison to traditional method (hit and trail methods). The futuristic application of the film will involve the management of an acute migraine.